Landscape development types in Central Lika 1980-2012 : applying spatial and process-oriented GIS model = Razvojni tipovi krajolika srednje Like 1980-2012 : primjena prostorno i procesno orijentiranog GIS-modela - Hamzić, Marta (Array, 2021)
This paper presents an analysis and definition of development types and subtypes in the landscape of Central Lika, based on processes of change in the period 1980−2012 CORINE Land Cover database data for 1980 and 2012 were used to establish the landscape types in Central Lika in those years. The landscape types in Central Lika were determined according to land cover/land use. Based on the mutual relations between the established landscape types in the two observed years, we established six landscape development types and three subtypes in Central Lika. The spatial distribution of landscape development types and subtypes in Central Lika was determined using the Standard Deviational Ellipse (Directional Distribution) spatial analysis method. The results obtained showed that in the observation period (1980−2012), most of the area of Central Lika (89.46%) belonged to the Stagnation landscape type. Other development types were present to a much lesser extent (about 5.5%) and were found to be Vegetation succession, Agrarisation, Vegetation degradation and Built-up land. We established a spatial gradation of three phases in the process of vegetation succession, that is, development subtypes from the centre to the margins of the research area. At the same time, in the observation period, the process and trend of extensification of land use in Central Lika was twice as present as intensification.